Application of Box-Behnken design in response surface methodology for the molecularly imprinted polymer pipette-tip solid phase extraction of methyl red from seawater samples and its determination by spectrophotometery. (December 2018) - Hashemi, Sayyed Hossein; Kaykhaii, Massoud; Keikha, Ahmad Jamali; Sajjadi, Zahra
Abstract: In this paper, a rapid, selective and effective technique, pipette-tip solid phase extraction based on molecularly imprinted polymer, was used for extraction and pre-concentration of methyl red (MR) prior to its determination by spectrophotometer. Variables influencing extraction efficiency including type and volume of eluent solvent, sample volume, number of cycles of extraction and elution, amount of sorbent and pH of the sample solution were optimized with two methods of one-variable-at-a-time and response surface methodology (RSM). For RSM optimization, seven factors in three-levels were utilized for Box-Behnken experimental design. Under optimum conditions, a linear calibration graph in the range of 3.0–300.0 μg L −1 for MR was resulted. The limit of detection of proposed method was 0.50 μg L −1 for MR. Finally, the investigated method was used for the determination of MR in seawater and the mean recoveries were calculated to be 84.0–98.0% with mean RSD of 2.5–6.7%. Graphical abstract: Highlights: An MIP-PT-SPE was developed and applied for preconcentration and spectrophotometry determination of methyl red in seawater. MIP was prepared using methacrylic acid as functional monomer and ethylene glycol dimethacrylate as cross-linker. The method was optimized using one-variable-at-a-time, response surface methodology and Box-Behnken experimental design. The ANOVA test showed that the experimental design model was in full agreement with experimental data.